2020
DOI: 10.5194/bg-2020-337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does drought advance the onset of autumn leaf senescence in temperate deciduous forest trees?

Abstract: Abstract. Severe droughts are expected to become more frequent and persistent. However, their effect on autumn leaf senescence, a key process for deciduous trees and ecosystem functioning, is currently unclear. We hypothesized that (I) severe drought advances the onset of autumn leaf senescence in temperate deciduous trees and that (II) tree species show different dynamics of autumn leaf senescence under drought. We tested these hypotheses using a manipulative experiment on beech saplings and three years of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Arend et al ., 2016b ; Fu et al ., 2019a , 2019b , 2019a , 2019b ; Zani et al ., 2020 ), complicating conclusive results about their respective effects and interactions. In addition, inconsistent results have been found for the progress of leaf senescence in response to moderate drought, hot spells and nutritional status under natural conditions in different species (Estiarte & Peñuelas, 2015 ; Xie et al ., 2018 ; Chen et al ., 2020 ; Mariën et al ., 2021 ), underscoring the importance of controlled experiments (but see Fu et al ., 2019a , 2019b , 2019a , 2019b ; Zani et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arend et al ., 2016b ; Fu et al ., 2019a , 2019b , 2019a , 2019b ; Zani et al ., 2020 ), complicating conclusive results about their respective effects and interactions. In addition, inconsistent results have been found for the progress of leaf senescence in response to moderate drought, hot spells and nutritional status under natural conditions in different species (Estiarte & Peñuelas, 2015 ; Xie et al ., 2018 ; Chen et al ., 2020 ; Mariën et al ., 2021 ), underscoring the importance of controlled experiments (but see Fu et al ., 2019a , 2019b , 2019a , 2019b ; Zani et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively reliable models exist to predict SOS based on accumulated temperature and photoperiod [8][9][10][11] . In contrast, long-term trends in autumn senescence are less clear 3,[12][13][14] , depend on EOS definitions based on senescence start, leaf discolouration stages, or dormancy 15,16 , and drivers are not well understood 6 . Although experimental evidence exists demonstrating that warm autumn temperatures delay leaf senescence 17 , long-term observations often do not show corresponding phenology trends in spite of persistent autumn warming 18,19 , but see 20 .…”
Section: Main Textmentioning
confidence: 99%
“…Manipulative experiments found that heat stress or dry air had no effect on the start of leaf shedding. (Mari€ en et al, 2021).…”
Section: Introductionmentioning
confidence: 99%